DRYLAND FARMING:A Concept of future agriculture - Arupratan Ghosh; P.K. Jana (LUDHIANA KALYANI, 2005)
This book required situation and conception of dryland farming.
DRYLAND FARMING GLOBAL SITUATION WATER CONSERVATION
Keywords: DRYDRYLAND FARMING, GLOBAL SITUATION ,WATER CONSERVATION